Genetic Diagnosis of Hereditary Hemorrhagic Telangiectasia: Four Novel Pathogenic Variations in Turkish Patients - Baysal, Mehmet (Balkan Med J, 2020)
AIMS: Hereditary hemorrhagic telangiectasia is an autosomal dominant disorder characterized by telangiectasia, epistaxis, and vascular malformations. Pathogenic mutations were found in ENG, AVCRL1, SMAD4, and GDF genes. In this study, we present our database of patients with hereditary hemorrhagic telangiectasia regarding the phenotype-genotype relations and discuss two novel ENG gene pathogenic variations in two unrelated families. METHODS: Next Generation Sequencing analysis was performed on the peripheral blood of nine patients with hereditary hemorrhagic telangiectasia in four unrelated families. All patients were diagnosed with hereditary hemorrhagic telangiectasia according to the Curaçao criteria. Data on treatment and screenings of visceral involvement were recorded from files. RESULTS: We have found a pathogenic variation in either the ENG or ACVRL1 gene in each family. Two novel pathogenic variations in the ENG gene, including NM_000118.3 (ENG): c.416delC (p.P139fs*24) and NM_000118.3(ENG): c.1139dupT (p.Leu380PhefsTer16), were found in the same family. The NM_000020.2(ACVRL1): c.1298C>T (p.Pro433Leu) pathogenic variation in the ACVRL1 gene in our first family and a novel heterozygous likely pathogenic NM_000020.2(ACVRL1): c.95T>C (p.Val32Ala) variation was found in our second family. Seven of the nine patients were treated with thalidomide for controlling bleeding episodes. All patients responded to thalidomide. In one patient, the response to thalidomide was lost and switched to bevacizumab. CONCLUSION: In hereditary hemorrhagic telangiectasia, certain types of mutations correlate with disease phenotypes and with next generation sequencing methods. New pathogenic variations can be revealed, which might help manage patients with hereditary hemorrhagic telangiectasia.